Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To determine which of the given functions are even, we need to recall that a function [tex]\( f(x) \)[/tex] is considered even if [tex]\( f(-x) = f(x) \)[/tex] for all [tex]\( x \)[/tex] in its domain. Let's analyze each function step-by-step to see if they satisfy this condition.
1. [tex]\( g(x) = (x - 1)^2 + 1 \)[/tex]:
We need to evaluate [tex]\( g(-x) \)[/tex]:
[tex]\[ g(-x) = ((-x) - 1)^2 + 1 \][/tex]
[tex]\[ = (-x - 1)^2 + 1 \][/tex]
[tex]\[ = (x + 1)^2 + 1 \][/tex]
[tex]\[ = (x^2 + 2x + 1) + 1 \][/tex]
[tex]\[ = x^2 + 2x + 2 \][/tex]
Now compare this to [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = (x - 1)^2 + 1 \][/tex]
[tex]\[ = (x^2 - 2x + 1) + 1 \][/tex]
[tex]\[ = x^2 - 2x + 2 \][/tex]
Clearly,
[tex]\[ x^2 - 2x + 2 \neq x^2 + 2x + 2 \][/tex]
Hence, [tex]\( g(x) = (x - 1)^2 + 1 \)[/tex] is not an even function.
2. [tex]\( g(x) = 2x^2 + 1 \)[/tex]:
Evaluate [tex]\( g(-x) \)[/tex]:
[tex]\[ g(-x) = 2(-x)^2 + 1 \][/tex]
[tex]\[ = 2x^2 + 1 \][/tex]
This matches [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = 2x^2 + 1 \][/tex]
So,
[tex]\[ g(-x) = g(x) \][/tex]
Hence, [tex]\( g(x) = 2x^2 + 1 \)[/tex] is an even function.
3. [tex]\( g(x) = 4x + 2 \)[/tex]:
Evaluate [tex]\( g(-x) \)[/tex]:
[tex]\[ g(-x) = 4(-x) + 2 \][/tex]
[tex]\[ = -4x + 2 \][/tex]
Now compare this to [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = 4x + 2 \][/tex]
Clearly,
[tex]\[ 4x + 2 \neq -4x + 2 \][/tex]
Hence, [tex]\( g(x) = 4x + 2 \)[/tex] is not an even function.
4. [tex]\( g(x) = 2x \)[/tex]:
Evaluate [tex]\( g(-x) \)[/tex]:
[tex]\[ g(-x) = 2(-x) \][/tex]
[tex]\[ = -2x \][/tex]
Now compare this to [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = 2x \][/tex]
Clearly,
[tex]\[ 2x \neq -2x \][/tex]
Hence, [tex]\( g(x) = 2x \)[/tex] is not an even function.
To summarize, the only even function among the given options is:
[tex]\[ g(x) = 2x^2 + 1 \][/tex]
1. [tex]\( g(x) = (x - 1)^2 + 1 \)[/tex]:
We need to evaluate [tex]\( g(-x) \)[/tex]:
[tex]\[ g(-x) = ((-x) - 1)^2 + 1 \][/tex]
[tex]\[ = (-x - 1)^2 + 1 \][/tex]
[tex]\[ = (x + 1)^2 + 1 \][/tex]
[tex]\[ = (x^2 + 2x + 1) + 1 \][/tex]
[tex]\[ = x^2 + 2x + 2 \][/tex]
Now compare this to [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = (x - 1)^2 + 1 \][/tex]
[tex]\[ = (x^2 - 2x + 1) + 1 \][/tex]
[tex]\[ = x^2 - 2x + 2 \][/tex]
Clearly,
[tex]\[ x^2 - 2x + 2 \neq x^2 + 2x + 2 \][/tex]
Hence, [tex]\( g(x) = (x - 1)^2 + 1 \)[/tex] is not an even function.
2. [tex]\( g(x) = 2x^2 + 1 \)[/tex]:
Evaluate [tex]\( g(-x) \)[/tex]:
[tex]\[ g(-x) = 2(-x)^2 + 1 \][/tex]
[tex]\[ = 2x^2 + 1 \][/tex]
This matches [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = 2x^2 + 1 \][/tex]
So,
[tex]\[ g(-x) = g(x) \][/tex]
Hence, [tex]\( g(x) = 2x^2 + 1 \)[/tex] is an even function.
3. [tex]\( g(x) = 4x + 2 \)[/tex]:
Evaluate [tex]\( g(-x) \)[/tex]:
[tex]\[ g(-x) = 4(-x) + 2 \][/tex]
[tex]\[ = -4x + 2 \][/tex]
Now compare this to [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = 4x + 2 \][/tex]
Clearly,
[tex]\[ 4x + 2 \neq -4x + 2 \][/tex]
Hence, [tex]\( g(x) = 4x + 2 \)[/tex] is not an even function.
4. [tex]\( g(x) = 2x \)[/tex]:
Evaluate [tex]\( g(-x) \)[/tex]:
[tex]\[ g(-x) = 2(-x) \][/tex]
[tex]\[ = -2x \][/tex]
Now compare this to [tex]\( g(x) \)[/tex]:
[tex]\[ g(x) = 2x \][/tex]
Clearly,
[tex]\[ 2x \neq -2x \][/tex]
Hence, [tex]\( g(x) = 2x \)[/tex] is not an even function.
To summarize, the only even function among the given options is:
[tex]\[ g(x) = 2x^2 + 1 \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.